PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM KERJA DAN MOTIVASI BERPRESTASI TERHADAP DISIPLIN KERJA GURU SMP NEGERI 18 PADANG - Sittinur sittinur; Syamsul Amar (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The purpose of this research are to analyze the effect of (1) the headmaster’s leadership on climate work, (2 the headmaster’s leadership and work climate on achievement motivation, and (3) the headmaster’s leadership, work climate and achievement motivation to discipline SMPN 18 Padan’s teachers. The population was teacher of SMPN 18 Padang are 62 peoples and sample are 51 people with Proportional stratified random sampling method. For the data analysis technique used was path analysis. The result are: headmaster’s leadership influence the  climate of work. the headmaster’s leadership, work climate and achievement motivation significantly influence teacher’s discipline. Achievement motivation has the greatest direct influence on discipline teachers compared with the principal's leadership and organizational climate. Teachers discipline are directly affected by the leadership that the principal function properly despite low achievement motivation of teachers. To improve labor discipline can be done by creating a conducive working environment even if the teacher does not have a high achievement motivation. Keyword: the headmaster’s leadership, work climate, achievement motivation and discipline